Comparative Analysis of the Financial Stability of Renewable-based Electricity Companies: The Case for Hydroelectric Organizations - Savchina, Oksana V.; Pavlinov, Dmitriy A.; Bobkov, Alexander L.; Konovalova, Natalia (International Journal of Energy Economics and Policy, 2022)
Hydroelectricity remains the dominate RES (Renewable Energy Source) and the most developed, reaching growth rate peaks in some countries in the 20th century. However, the share of it has fallen over the last few years, as other renewable sources have received rapid development. Despite this, growth for hydroelectricity has remained stable, with China, India, Japan, Russia, Turkey, France, Norway, Canada, USA and Brazil as market leaders. This article analyzes the key trends of development of the hydroelectricity market as a whole, as well as the financial stability of its organizations using bankruptcy likelihood prediction models. The Brazilian and Russian companies were chosen to assess as both countries are classified as developing markets. The bankruptcy prediction models indicate that overall, the financial stability of hydroelectricity giants of Brazil and Russia is at a high level, though profitability ratios are very low. During the COVID-19 pandemic, several financial support measures were implemented by governments, along with the already existing instruments for stimulating renewable energy growth. Authors’ forecasts show that current trends on the market indicate that net addition capacity growth in the next few years will not be enough to meet Net Zero goals for the renewables market.